Great Tit (Parus major) Nestlings Have Longer Telomeres in Old‐Growth Forests Than in Young Forests - Ronalds Krams; Dina Cīrule; Maris Munkevics; Sergejs Popovs; Priit Jõers; Jorge Contreras Garduño; Indrikis A. Krams; Tatjana Krama (Ecology and Evolution)
ABSTRACT Modification and deterioration of old‐growth forests by industrial forestry have seriously threatened species diversity worldwide. The loss of natural habitats increases the concentration of circulating glucocorticoids and incurs chronic stress in animals, influencing the immune system, growth, survival, and lifespan of animals inhabiting such areas. In this study, we tested whether great tit (Parus major) nestlings grown in old‐growth unmanaged coniferous forests have longer telomeres than great tit nestlings developing in young managed coniferous forests. This study showed that the patches of young managed coniferous forests had lower larval biomass than old‐growth forests. Since insect larvae are the preferred food for great tit nestlings, the shortage of food may divert energy resources away from growth, which can show up as physiological stress, often raising the heterophil/lymphocyte (H/L) ratio. The H/L ratio revealed a significant difference in stress levels, being the highest in great tit nestlings developing in young‐managed pine forests. We also found that the development of great tit nestlings in young managed forests had significantly shorter telomeres than in old‐growth forests. Although nestling survival did not differ between the habitats, nestlings growing up in old‐growth forests had greater telomere lengths, which can positively affect their lifespan. Our results suggest that the forest habitats affected by industrial forestry may represent ecological traps, as the development of young birds in deteriorated environments can affect the age structure of populations.